2019
DOI: 10.1016/j.celrep.2019.06.018
|View full text |Cite
|
Sign up to set email alerts
|

Nitric Oxide Modulates Metabolic Remodeling in Inflammatory Macrophages through TCA Cycle Regulation and Itaconate Accumulation

Abstract: Summary Classical activation of macrophages (M(LPS+IFNγ)) elicits the expression of inducible nitric oxide synthase (iNOS), generating large amounts of NO and inhibiting mitochondrial respiration. Upregulation of glycolysis and a disrupted tricarboxylic acid (TCA) cycle underpin this switch to a pro-inflammatory phenotype. We show that the NOS cofactor tetrahydrobiopterin (BH 4 ) modulates IL-1β production and key aspects of metabolic remodeling in activated murine macrophages… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
161
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 189 publications
(171 citation statements)
references
References 52 publications
10
161
0
Order By: Relevance
“…When cells are exposed to LPS, the production of nitric oxide (NO) blocks mitochondrial respiration, thus forcing glycolysis to sustain the production of ATP 18,26 . When nitrite levels were measured, we found that oxPAPC administration to LPS-treated macrophages shuts down NO production in a dose-dependent manner, relative to its production in those treated with LPS only (Fig.…”
Section: Respiration Maintenance Promoted By Oxpapc Enables Lps-stimumentioning
confidence: 99%
“…When cells are exposed to LPS, the production of nitric oxide (NO) blocks mitochondrial respiration, thus forcing glycolysis to sustain the production of ATP 18,26 . When nitrite levels were measured, we found that oxPAPC administration to LPS-treated macrophages shuts down NO production in a dose-dependent manner, relative to its production in those treated with LPS only (Fig.…”
Section: Respiration Maintenance Promoted By Oxpapc Enables Lps-stimumentioning
confidence: 99%
“…Itaconate is delivered from the mitochondria to the nucleus via an unknown transport mechanism, where its electrophilic properties promote activation of tolerance signaling pathways, including increased expression of the A20 ubiquitin ligase that inhibits NFκB p65 proinflammatory transcription factor and activates NF erythroid 2‐related factor (Nrf2), a vital regulator of cellular redox balance . The specific mechanisms responsible for diverting citrate to itaconate are unknown, but one candidate is direct redox signaling …”
Section: Introductionmentioning
confidence: 99%
“…34 The specific mechanisms responsible for diverting citrate to itaconate are unknown, but one candidate is direct redox signaling. 37 We recently defined the sequential time-dependent rewiring of immunometabolism and mitochondrial bioenergetics during sepsis-like inflammatory responses using unbiased metabolomics and integrated bioinformatics in THP-1 human monocytes. 38 In that study, we temporally divided inflammatory responses into early anabolic resistance metabolic rewiring (0-8 h), the nutrient switch to catabolic lipolytic and proteolytic tolerance rewiring (24-48 h), and a partial resolution rewiring of the anabolic/catabolic state (72-96 h), typical of septic shock in animals and humans.…”
mentioning
confidence: 99%
“…Under normoxic conditions, the LPS-triggered HIFα accumulation depends on nuclear factor (NF)-κB-and p42/44 MAPK-dependent signal transduction [69,70]. Ultimately, this results in PHD inhibition via (i) enhanced ROS and RNS production [71][72][73][74], (ii) metabolic inhibition of PHD by succinate accumulation [75], and/ or (iii) decrease of availability of the PHD cofactor Fe 2+ [3]. Adding another layer of complexity, HIF activation induced by LPS leads to a distinct and different response of myeloid cells compared to hypoxia-driven HIF activation [76].…”
Section: Inflammatory and Infectious Hifα Stabilizationmentioning
confidence: 99%